Gangster = Edwin Boyd - Cosens, Steve ca. 20. Jh; Speedman, Scott 1975-; Reilly, Kelly 1977-; Cox, Brian 1946-; Durand, Kevin 1974-; Cross, Joseph 1986-; Mapother, William 1965-; Fletcher, Brendan 1981-; Sullivan, Charlotte 1983- (2013)
WWII vet Eddie Boyd is torn between providing for his young family and an unfulfilled dream of becoming a Hollywood star. He discovers a way to do both, but his dream leads him down a path of danger and tragedy.
Bildformat: widescreen
Orig.: Kanada, 2011
Keywords: Crime films; Biographical films; Kriminalfilm; Gangsterfilm; Biografischer Film; Bankräuber; Veteran; Gangster; Film; DVD-Video